On the Continuous Delivery in IoT Systems - Pereira, Igor Muzetti (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2022: Anais do XXV Congresso Ibero-Americano em Engenharia de Software, 2022)
The development of IoT systems brings the adequacy of software engineering to current paradigms, such as IoT, industry 4.0, smart cities and environments, and wearable devices. IoT systems require the integration of different technologies such as sensors, actuators, edge devices, cloud computing, big data, artificial intelligence, and IT operations. The successful delivery of products depends directly on the continuous cooperation of professionals with different skills. However, we noticed a specific resistance in carrying out continuous and automated software deliveries to hardware devices by professionals. This research investigates the practices and technologies for the continuous software delivery pipeline on hardware devices that make up an IoT system.